2011
DOI: 10.1007/s11739-011-0624-5
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of renal artery stenosis in patients undergoing cardiac catheterization

Abstract: To investigate the prevalence of significant renal artery stenosis (RAS ≥50%), and to identify clinical predictors for significant RAS in patients with an elevated cardiovascular risk, such as those affected by ischemic heart disease. In patients with an elevated cardio-vascular risk, both atherosclerotic renovascular disease and coronary artery disease (CAD) are likely to occur. Prospectively from April 2007 to March 2008, all consecutive patients with ischemic heart disease undergoing non-emergent cardiac ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
3
12
2
Order By: Relevance
“…We evaluated the relationship between renal artery diameters, either RD or MD, RAS and cardiovascular events in 623 subjects with ischemic heart disease of the RAS-CAD cohort [11,12]. We reported that the incidence of cardiovascular events was increased in subjects with low-to-moderate renal artery stenosis and that, in these subjects, those with reduced MD had a significantly increased GFR-independent risk to develop a first cardiovascular event independently.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We evaluated the relationship between renal artery diameters, either RD or MD, RAS and cardiovascular events in 623 subjects with ischemic heart disease of the RAS-CAD cohort [11,12]. We reported that the incidence of cardiovascular events was increased in subjects with low-to-moderate renal artery stenosis and that, in these subjects, those with reduced MD had a significantly increased GFR-independent risk to develop a first cardiovascular event independently.…”
Section: Discussionmentioning
confidence: 99%
“…The design and selection criteria for the RAS-CAD cohort has been detailed previously [12]. Briefly, prospectively from March 2006 for 1 year, as part of a diagnostic cardiac catheterization study, the RAS-CAD study (NCT 01173666) [11], all consecutive patients affected by ischemic heart disease, referred to the Cardiac Catheterization laboratories of the Division of Cardiology, University of Catania, with a clinical indication for coronary angiography for symptomatic angina or positive findings on a cardiac functional test, underwent coronary and renal arteriography during the same angiographic session.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations